DYNAMICS OF THE MOST INFLUENTIAL POLITICIANS OF THE REPUBLIC OF KHAKASSIA (BY RESULTS OF MONITORING EXPERT POLLS OF 1998–2014) - Zlotkovskij, Vladimir Il’ich (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2017)
The article aims to identify the most influential Republican politicians that determine the direction of political solutions in the region and ensuring their implementation. Relevance of a subject of a research is caused by a crucial role of political elite in social and economic and political development of Khakassia. Novelty is caused by limitation of number of scientific publications on the lifted problem. The used methods – expert polls and electoral statistics. The following conclusions are drawn by results of the conducted researches. First, line items of heads of managerial and economic structures in the top ten of the most influential republican politicians during the researched period underwent to essential transformation. In 1998, there was a rare situation in the Russian practice heavily on the political elite of the economic elite in the name of the representatives of the leading industrial enterprises of Khakassia – Sayan Aluminum Plant. Over time, the situation has changed in 2009. was set up regional “party of power” in the face of the Republican government and the party “United Russia”, around which all the relevant actors of regional political process. Secondly, engaging the top positions in the power structures necessary but not sufficient condition for the occurrence of the most influential Republican politicians. This number does not include bank and trade union officials, media executives and university leaders of political parties, with the exception of “United Russia”, public organizations and associations. Third, in recent years, as part of the 30 most influential politicians intensified the “political weight” of the leaders of the republican government and the law enforcement system and decreased – employees legislative authorities, media leaders and heads of local self-government. Fourthly, results of monitoring expert polls on determination of the leading republican politicians act as the effective tool for understanding and forecasting of regional political process.